Sensitivity Analysis of PCDR35 Radar - Rejfek, Luboš; Fišer, Ondřej; Matoušek, David; Beran, Ladislav; Chmelař, Pavel (Croatian Society Electronics in Marine - ELMAR, 2017)
This conference paper is aimed at the analysis of the frequency modulated interrupted continuous wave radar (PCDR35). This radar was developed under the Institute of Atmospheric Physic Czech Academy of Sciences leadership. A primary aim of this radar is the monitoring of meteorological targets (rain cells, hail stones and other). In this paper a radar measurement of the corner reflector with the theoretical reflectivity determination are compared. In the last part of this paper an evaluation of this radar and possible modifications (classical FMCW) are described.
Citlivostní analýza radaru PCDR35
Keywords: FMICW radar; spectral analyse; meteorological targets; radar sensitivity; radar validation